Optic Nerve Regeneration - Benowitz, Larry (2010)
Retinal ganglion cells (RGCs) are normally unable to regenerate their axons after optic nerve injury or degenerative disorders, resulting in lifelong visual losses. This situation can be partially reversed by activating RGCs’ intrinsic growth state, maintaining their viability, and counteracting inhibitory signals in the extracellular environment. Advances over the past few years continue to extend the amount of regeneration that can be achieved in animal models. These findings lend hope to the possibility that clinically meaningful regeneration may become a reality within a few years provided that regenerating axons can be guided to their appropriate destinations.